2021
DOI: 10.4269/ajtmh.21-0255
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Peru as a Result of the COVID-19 Pandemic: Perspective from a Country with Limited Internet Access

Abstract: The COVID-19 pandemic contributed to the worldwide implementation of telemedicine because of the need for medical care for patients, especially those with chronic diseases. This perspective paper presents the current situation of telemedicine in Peru, showing advances in regulation, cases of successful implementation, and the current challenges. Access to health should be available to all, and more efforts need to be implemented to offer access to the internet to achieve high-quality telemedicine to all the vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 78 publications
(99 reference statements)
1
42
0
6
Order By: Relevance
“…11 Similarly, anxiety of the educators was associated with government effectiveness in our study. Thus, our finding was in accordance with the study done by Alvarez-Risco et al 10 Further, the study made by Alvarez-Risco et al 12 on the COVID-19 pandemic created an opportunity to expand telemedicine services. Alvarez-Risco et al 12 foresee that telemedicine in Peru could help fortify disease prevention programs, monitor chronic disease patients, and combat malnutrition in vulnerable populations, such as pregnant women and children under 5 years old.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…11 Similarly, anxiety of the educators was associated with government effectiveness in our study. Thus, our finding was in accordance with the study done by Alvarez-Risco et al 10 Further, the study made by Alvarez-Risco et al 12 on the COVID-19 pandemic created an opportunity to expand telemedicine services. Alvarez-Risco et al 12 foresee that telemedicine in Peru could help fortify disease prevention programs, monitor chronic disease patients, and combat malnutrition in vulnerable populations, such as pregnant women and children under 5 years old.…”
supporting
confidence: 92%
“…Yáñez et al 9 have reported that their results can help guide mental health service providers toward vulnerable groups of healthcare workers that are closer to Lima, the COVID-19 epicenter in Peru. Further, Alvarez-Risco et al 10 reported that Peru was forced into telemedicine due to the pandemic, and the government is working to improve Internet coverage.…”
Section: The Negative Effects Of Covid-19 On Health Professionalsmentioning
confidence: 99%
“…For instance, there is no mention of the effects the lack of KAP has already caused in Peru. Examples of some studies include: Infodemic 1 , 2 , 3 Self-medication 4 , 5 Medicinal plants use 6 , 7 , 8 , 9 Use of unproven treatments such as chlorine dioxide 6 , 10 Issues in children with the development of MIS-C 11 , 12 , 13 , 14 Impact in mental health 15 , 16 , 17 , 18 , 19 Technostress 20 Issues in adequate implementation of public health measures 21 , 22 , 23 Furthermore, Peru is leading some interesting aspects compared to Latin America in the implementation of telemedicine 24 , 25 , 26 , 27 …”
mentioning
confidence: 99%
“…The Peruvian response to the pandemic was an early lockdown with a set of prohibitions and mobility restrictions. There are several ways in which the pandemic affected Peruvians' livelihoods, mental health, and information technology development, among others [40][41][42]. According to [40], Peru reached a milestone of more than 1200 deaths per one million of inhabitants by February 2021.…”
Section: Covid-19 Pandemic In Peru: a Brief Reviewmentioning
confidence: 99%
“…However, the authors argue that Peru could control the info-demic due the introduction of prison sentences to discourage creating and sharing fake news. Finally, following [42], there were good advances in digitalization that were caused by the pandemic; nevertheless, more efforts are needed to implement telemedicine and to offer access to the internet to achieve high-quality telemedicine to all vulnerable groups in Peru.…”
Section: Covid-19 Pandemic In Peru: a Brief Reviewmentioning
confidence: 99%